Analysis of the Influence of Macroeconomic Variables and Internal Bank Performance on the Profitability of Islamic Banking in Indonesia - Sa'diyah, Rismawati; Nasrulloh, Nasrulloh (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2025)
This study aims to examine and analyze the profitability level of Islamic banking in Indonesia by considering macroeconomic conditions, such as inflation, the BI-Rate, and exchange rates, as well as the internal performance of Islamic banks, including CAR, FDR, and BOPO. The research adopts a quantitative methodology with a time-series data analysis covering five years (2019–2023), comprising 60 samples. Data analysis uses the VECM method and the Granger Causality Test to identify causal relationships between variables. Additionally, the study employs Impulse Response Functions and Variance Decomposition to determine the magnitude of variable impacts. The study results indicate that macroeconomic conditions and internal bank characteristics significantly impact efforts to enhance the profitability of Islamic banking. In the short term, the CAR, BOPO, FDR, and exchange rate variables have an insignificant negative effect. Conversely, inflation exhibits a significant positive relationship, while the BI Rate has an insignificant positive effect on improving Islamic banking profitability. In the long term, the CAR, FDR, and inflation variables negatively influence Islamic banking profitability, whereas BOPO has an insignificant positive impact. On the other hand, the BI Rate and exchange rate variables show a relatively significant positive effect. However, these variables collectively substantially impact the profitability of Islamic banking in Indonesia. Bank Indonesia and other financial authorities can utilize the research findings to design more responsive policies to maintain the profitability of Islamic banking. This study provides empirical evidence that can assist Islamic banks in risk management strategies and financial planning.